ANALISIS PERUBAHAN PENDAPATAN USAHA PEDAGANG ECERAN SEBELUM DAN SESUDAH BERDIRINYA INDOMARET DAN ALFAMART DI KECAMATAN TAMPAN PEKANBARU - Trisdiana M.Nur; Azwar Harahap; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Minimarket very rapid growth with increasing human need for daily living needs, as well as the advancement of science and technology, minimarket for the community is needed to meet the basic needs of daily. Minimarket rapidly growing into residential areas, negatively impact the existing retailers in the region. This study aims to determine the change in income before and after the establishment Indomaret And Alfamart, as well as to determine whether there are differences in the price of similar products sold in Indomaret, Alfamart and retail traders.This research was conducted in four scattered village in District Tampan Pekanbaru. Direct interviews conducted to 76 respondents retailers who becomes the object of study, research was conducted by descriptive qualitative, and to support in view of the differences of income before and after as well as differences in the price of similar products sold then in use quantitative analysis using a different test (t test ) with α = 0.05. The results showed a significance value (0.000) <0.05, mean that there are differences in income retailers before and after the Indomaret and Alfamart. While the difference in the price of cigarettes product types significance value (0.782)> 0.05 means that there is no difference between the price of cigarettes Indomaret product types, Alfamart and retailers. As well as the types of beverage products there is no significant price difference, is seen from the significant value > 0.05 is (0.857).Keywords: Income, Changes in profit, price, and distance.